FMEA Approach of Lean Sig Sigma Implementation: Estimating the Value of COPQ - Purwadi; Y, Syaharuddin; Sampeliling, Alexander (International Journal of Psychosocial Rehabilitation, 2020)
Lean and Six Sigma are comprehensive concepts in business systems. The strength of this concept is that it is able to provide tangible results for the company, so it requires implementation and measurable evaluation steps. The implementation step of Lean Six Sigma must use two approaches: a lean approach to eliminate waste processes and reduce variations in products. This article discusses the changes resulting from the implementation of Lean Six Sigma because there are differences in the cost of quality between the conditions before and after the implementation. Cost of Poor Quality (COPQ) is the cost due to defects in processes, products, and services. COPQ is defined as the costs that must be incurred to resolve failures and damage in the process. The measurement method used to estimate the value of CPOQ requires initial measurements. The constraint faced in this estimation was that there was no measure available at the start of the project. To overcome these limitations, we use a weighted risk approach based on potential failures to calculate the costs of the ongoing process. Furthermore, the paper also presents the steps in Lean Six Sigma. In addition, the evaluation mechanism uses Lean Six Sigma with the FMEA approach to COPQ.